Moving pattern of Zophobas beetle through physical stimulation at elytra - Tan, Pak Zan (2019)
This project aims to provide necessary information about the movement path of a beetle when encountering obstacles in different directions. This information will be useful for researchers to create a walking Cyborg Beetle with a better navigation system. This project contains a literature review, setup and development of workstation, experiment procedure, analysis on the physical stimulation on the beetle and future research and study.